Rapid Detection of the Poly-γ-d-Glutamic Acid Capsular Antigen of Bacillus anthracis by Latex Agglutination - AuCoin, David P. (2009)
Latex agglutination has been used to detect capsular polysaccharides from a variety of bacteria in body fluids. A latex agglutination assay was constructed for detection of the poly-γ-d-glutamic acid (γdPGA) capsular polypeptide of Bacillus anthracis in serum from animal models of pulmonary anthrax. The assay was able to detect γdPGA in serum from infected animals at concentrations of 100–200 ng/ml.